Análisis del influjo en el caso Macondo con el fin de generar recomendaciones para ser aplicadas en el caribe colombiano (2019)
In this activity the safety factor must be even higher because it is a location with difficult access, dealing with the safety and integrity of human lives and time of external help response to possible accidents. In this document, it study the accident that occurred in 2010, in the Deepwater Horizon platform with the Macondo well in the Gulf of Mexico, providing information for its contextualization in its objective or target geological as in its geographical location. A compilation of information about the type of platform in which it was located and are established the most representative risks for a semi-submersible platform; and finally are selected and analyzed by a proposed root cause analysis due to which is carried out in different schemes immersed in the accident of the case study, such as the RAM matrix for risk assessment, a map of the facts for specify each of the events that occurred to reach the fatal accident, a Fishbone diagram showing the causes and a cheese diagram Swiss to represent the barriers to which they were lost. Finally, because Colombia is starting its offshore projects, it is carried out a compilation of regulations to generate a series of recommendations with based on the analysis carried out for the Macondo case.